Cultural Radicalization Cons as an Effort to Eradicate the Crime of Terrorism in Indonesia - Arifin, Samsul; Achmad Hariri; Satria Unggul Wicaksana Prakasa; Asis, Asis (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Radicalism, which is the main root of a person becoming a terrorist, is a fact that to fight the spread of radicalism, law enforcement is not enough. On the one hand, social conditions also significantly influence efforts to counteract radicalism. From these problems, the question of this research is how socio-culture works in counteracting radicalism. The method used in this study is Socio-legal-based legal study. Further, this study aims to understand and elaborate that socio-culture influences efforts to fight the spread of radical ideas and eradicate criminal acts of terrorism in Indonesia. The results of this study show that in society, there has been cultural radicalization cons through community activities, which have succeeded in countering the spread of radicalism.